Axial load resistance of grouted sleeve connection for modular construction. (September 2020) - Dai, Ziquan; Pang, Sze Dai; Liew, JY Richard
Abstract: Modular construction has become popular for its advantages in construction efficiency and reduced manpower on site. Steel modules are typically connected using bolted connections which often suffer from inadequate allowable tolerances to accommodate imperfections due to vertical alignment of modules. To solve these problems, a shear-keyed grouted sleeve connection (SK-GSC) is proposed to connect the square hollow section (SHS) columns between the upper and lower modules. This paper investigates the axial performance of SHS SK-GSCs, specifically on their resistance and load transferring mechanism. To study the effect of shear key spacing, grout strength, and grout thickness, fifteen specimens were tested, and numerical models were calibrated against the test results to gain insight into the failure mechanism. It was found that the load-bearing resistance of SHS SK-GSCs was contributed by the frictional bond at the steel-grout interface and the diagonal compression struts developed in the grout. The proposed connections have sufficient axial resistance, stiffness and ductility to integrate the module columns vertically as compared to existing bolted connections. They were robust enough to withstand potential tension force due to accidental action in the design of modular buildings. Highlights: Shear-keyed grouted sleeve connection is proposed for steel modular construction. The proposed connection provides greater tolerance for installation of modules. The strength, stiffness, ductility and failure mechanism of the connection are studied numerically and experimentally. The proposed connection shows superior structural performance for application in high-rise steel modular buildings.